Muscle Injuries in Sport Athletes : Clinical Essentials and Imaging Findings - Roger, Bernard; Guermazi, Ali; Skaf, Abdalla (Sports and Traumatology, 2017)
This book attempts to provide a comprehensive look at all of the pathologies of muscles that are likely to be encountered in treating sports-related injuries. Its purpose is to give the practitioner a guide for identifying injuries and choosing the best therapeutic strategy. The first part presents the consensus view of current knowledge: the physiology of lesions and their prognosis as well as their anatomy, clinical imaging, and treatment. Then each of the muscles is described in turn, with a review of anatomy, clinical examination, the results of imaging, and therapeutic choices for acute and chronic injuries. A major section is dedicated to imaging, with the emphasis on which diagnostic methods are best for specific injuries and how to use diagnostic imaging to determine the most suitable therapeutic strategies. Special care has been taken to provide high-quality illustrations that clearly show how to identify the lesion of the damaged muscle. A wealth of illustrations, many in color, are included. Finally, the book concludes with some clinical cases and technical notes relevant to treatment of sports-related muscle injuries.